2018
DOI: 10.1094/pdis-01-18-0074-re
|View full text |Cite
|
Sign up to set email alerts
|

The Colonization Process of Sunflower by a Green Fluorescent Protein-Tagged Isolate of Verticillium dahliae and its Seed Transmission

Abstract: Sunflower Verticillium wilt is a widespread and destructive disease caused by the soilborne pathogen Verticillium dahliae. To better understand the process of infection and seed transmission of the fungus, sunflower roots were inoculated with a V. dahliae strain (VdBM9-6) labeled with green fluorescent protein (GFP) and monitored microscopically. After 24 to 96 h postinoculation (hpi), conidia germinated and developed into mycelium on root hairs, elongation zones, and caps of lateral roots. Mycelium colonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…This result indicated that sunflower seed coats are the major carriers for long-distance transmission of seed-borne pathogens. Verticillium dahliae was detected in almost all the sampled sunflower varieties collected (84%), which suggests that seed-to-seed transmission and long-distance transmission of the fungi is carried out by the seed coat, as seen in spinach production [12]. The presence of multiple fungi on the seed coats supports the fact that seed contamination is the main machinery for the long-distance transmission of seed-borne fungal diseases [7,8,11,31].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This result indicated that sunflower seed coats are the major carriers for long-distance transmission of seed-borne pathogens. Verticillium dahliae was detected in almost all the sampled sunflower varieties collected (84%), which suggests that seed-to-seed transmission and long-distance transmission of the fungi is carried out by the seed coat, as seen in spinach production [12]. The presence of multiple fungi on the seed coats supports the fact that seed contamination is the main machinery for the long-distance transmission of seed-borne fungal diseases [7,8,11,31].…”
Section: Discussionmentioning
confidence: 74%
“…Results from previous research on the contamination process of sunflower verticillium wilt using GFP (green fluorescent protein) -labeled V. dahliae showed that the seed coat was one of the main tissues where V. dahliae inoculum infect and accumulate [12]. This finding led us to find out the rate of contamination among commercial sunflower varieties with emphasis on their seed coats.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations